STUDI ANALISIS KURIKULUM ILMU FALAK UIN ALAUDDIN MAKASSAR BERBASIS INTEGRASI ASTRONOMI - Primantyas, Bagus Herdianto; Wakia, Nurul; HR, Sabriadi (HISABUNA: Jurnal Ilmu Falak, 2026)
ABSTRACT This re$se$arch focuse$s on analyzing the$curriculum$of phalac scie$nce$at the$State$Islam$ic Unive$rsity of Alauddin M$akassar base$d on astronom$y inte$gration. The$form$ulation of this proble$m$include$s: how is the$curriculum$of phalac scie$nce$at Alauddin M$akassar State$Islam$ic Unive$rsity, how is the$astronom$ical inte$gration of the$curriculum$of phalac scie$nce$at Alauddin M$akassar State$Islam$ic Unive$rsity. This re$se$arch use$s a library re$se$arch m$e$thod by analyzing the$astronom$y inte$gration-base$d astrophysics curriculum$through source$s obtaine$d from$books, article$s, the$se$s, and re$ports on pre$vious re$se$arch re$sults that are$re$le$vant to this re$se$arch. The$re$sults of this study are$the$re$alistic le$arning of astrophysics applie$d by the$Falak Scie$nce$Study Program$at Alauddin M$akassar State$Islam$ic Unive$rsity has 63 course$s with 147 cre$dits consisting of 13 Unive$rsity com$pulsory course$s, 22 Faculty course$s and 26 Falak Scie$nce$Study Program$course$s. Of the$26 course$s in the$Falak Scie$nce$Study Program$that ne$e$d to be$adde$d are$13 course$s, nam$e$ly Lunar E$clipse$Hisab, Solar E$clipse$Hisab, Non-Optic Rukyat De$vice$s, Optical Rukyat De$vice$s, Advance$d Falak Scie$nce$Te$xt Studie$s, Hisab and Rukyat Practice$s, Basics of Astronom$y, Basics of Sphe$rical Astronom$y, Basics of Physics, M$athe$m$atics. Hisab Rukyat Study of Diffe$re$nt Countrie$s, Astronom$y and Culture$, Calculator Algorithm$s and Program$m$ing, Com$pute$r Algorithm$s and Program$m$ing (E$xce$l), Com$pute$r Algorithm$s and Program$m$ing (VB and Android), and Statistics. The$im$plication of this re$se$arch is that the$Falak Scie$nce$Study Program$is e$xpe$cte$d to re$duce$le$gal course$s to fit the$focus of the$acade$m$ic fie$ld and re$vie$w or re$vie$w the$e$xisting curriculum$at othe$r unive$rsitie$s. Keywords: Astronomy Integration, Curriculum, Falak Science